Application of pinch technology through a computational program for planning a heat exchanger network - Brandão, Yago Fraga Ferreira; Correia , João Henrique Lewi Accioly; Marques, José Antônio (Brazilian Journal of Production Engineering, 2022)
Pinch technology is a methodology used in the optimization and dimensioning of heat exchanger networks, initially developed by Hohnmann and Linnhoff during the oil crisis in the mid 70’s and 80’s. With greater energy efficiency and consumption reduction. In this work, a computational algorithm was developed using the Matlab tool and its extension for process simulation, Simulink, in order to apply the principles of Pinch technology in the computational resolution of a problem situation involving a network of heat exchangers. Initially, a problem situation involving Pinch technology was selected, which was solved by traditional method. From this, the computational algorithm was developed in Matlab, based on the principles of Pinch technology and using data belonging to the problem selected for study; performing a comparison of the original data and those found by the algorithm to validate the developed program. After validating the Matlab algorithm, Simulink was used to develop a program in block language, to provide a better graphic visualization of the obtained results, comparing them again with the results of the traditional method. The results obtained by the algorithms in Matlab / Simulink were the same ones obtained by the traditional method, thus validating the programs developed in this research, thus being able to assist future works that aim to deepen the computational application of Pinch technology.